2018
DOI: 10.1186/s12943-018-0851-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PDHX by microRNA-27b deregulates cell metabolism and promotes growth in breast cancer

Abstract: BackgroundThe disruption of normal gene regulation due to microRNA dysfunction is a common event in cancer pathogenesis. MicroRNA-27b is an example of an oncogenic miRNA, and it is frequently upregulated in breast cancer. MicroRNAs have been found to deregulate tumor metabolism, which typically manifests as heightened cellular glucose uptake in consort with increased flux through glycolysis, followed by the preferential conversion of glycolytic pyruvate into lactate (a phenomenon known as the Warburg Effect). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…Phosphorylation‐dependent inhibition of PDH is a related event in this process. PDH plays a crucial regulatory role by tuning glycolytic metabolism in cancer cells . Enhanced glycolysis inhibited pyruvate dehydrogenase flow, and downregulated TCA cycle labeling, consistent with the Warburg effect .…”
Section: Discussionmentioning
confidence: 95%
“…Phosphorylation‐dependent inhibition of PDH is a related event in this process. PDH plays a crucial regulatory role by tuning glycolytic metabolism in cancer cells . Enhanced glycolysis inhibited pyruvate dehydrogenase flow, and downregulated TCA cycle labeling, consistent with the Warburg effect .…”
Section: Discussionmentioning
confidence: 95%
“…Since then, numerous studies have demonstrated that the occurrence of mutations in PDHX gene are due to PDH deficiency [24][25][26]. In addition, PDHX is inhibited by miR-27b and regulates the metabolic proliferation of breast cancer cells, which leads to reduced patient survival [27].…”
Section: Introductionmentioning
confidence: 99%
“…This function was supported by anti-type II diabetes (T2D) drug metformin, that counteracted the generation of CSCs [189]. MiR-27b was also shown to promote the Warburg effect, by inhibiting the PDHX with subsequent dysregulation of the levels of pyruvate, lactate and citrate that increase cell proliferation in the Luminal A and TNBC subtypes [190].…”
Section: Other Non-coding Rnas Relevant In Breast Cancermentioning
confidence: 99%